Penguatan Literasi Keuangan Syariah bagi Masyarakat Nelayan di Kota Palopo - Muh. Akbar; Andi Achmad Syam; Nurman Nurman; Asti Annisah Futri (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
Written This community engagement program aims to enhance Islamic financial literacy for the fishing community in Binaan Lazismu Village, Palopo City, through a collaboration between Lazismu Palopo and Bank Syariah Indonesia (BSI). The low understanding of Islamic finance among coastal communities has limited the utilization of formal financial services, particularly regarding savings, financing, and other sharia-based financial instruments. The implementation method included interactive workshops, group discussions, demonstrations of Islamic banking products, and assistance in preparing simple family budgeting plans. The results show an increase in participants’ knowledge of Islamic financial principles, understanding of sharia banking contracts, and awareness of planned family financial management. Participants also expressed interest in utilizing Islamic savings products and digital banking services introduced during the session. The activity successfully strengthened Islamic financial literacy and encouraged financial inclusion in coastal communities. Follow-up programs are needed to ensure sustainable financial behavior change